Media and the issues of environment - Mohd Yusof Hj Othman (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2010)
Environmental issue is one of dominance issues in most mass media of today. However, the media can also create awareness to their readers, and contribute to the positive perception on the issue. Apart from just merely reporting what happen to the environment, mass media can also change the attitude of their readers, and forms the opinion of the readers so that they can act proactively. This can be observed in three different ways; media and culture, media and language, and media and public perception. Four main activities toward better management of the environment are; forest management, water management, energy management, and waste management. This paper discusses this issue in order to develop reading habit among members of society who are sensitive on the issue of environment